1993
DOI: 10.1002/jsfa.2740630209
|View full text |Cite
|
Sign up to set email alerts
|

Effects of processing and storage on some chemical characteristics and lipid composition of a ghanaian fermented fish product

Abstract: Abstract:To evaluate the effectiveness of the traditional method of processing in preservation of the final product, the changes in composition of lipids, free amino acids and organic acids of 'momoni', a Ghanaian fermented fish product, were investigated using Japanese jack mackerel (Trachurusjaponicus) which is similar to African jack mackerel (Curanx hippos). The moisture content decreased drastically from 751 to 505 g kg-I after fermentation for 3 days, and then remained almost constant during subsequent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…Sundried shrimps would also find favour in the prevention of many human diseases including cancer, atherosclerosis, stroke, rheumatoid arthritis, neurodegeneration, and diabetes [Fang et al, 2002]. Yankah et al [1993] found raised histidine level in salted fish when sundried. Histidine is essential for children but its indispensability remains unresolved in healthy adult [FAO/WHO/UNU, 1985].…”
Section: Non-polar Fatty Acids Concentrationmentioning
confidence: 99%
“…Sundried shrimps would also find favour in the prevention of many human diseases including cancer, atherosclerosis, stroke, rheumatoid arthritis, neurodegeneration, and diabetes [Fang et al, 2002]. Yankah et al [1993] found raised histidine level in salted fish when sundried. Histidine is essential for children but its indispensability remains unresolved in healthy adult [FAO/WHO/UNU, 1985].…”
Section: Non-polar Fatty Acids Concentrationmentioning
confidence: 99%
“…The quantities of individual amino acids were determined on a Technicon Sequential Multiple (TSM) amino acid analyser. Salt content was determined according to the method of Yankah et al (1993). Minced momoni sample (0.5 g) was digested with 20 mL of concentrated HNO 3 for 2 h at 1001C.…”
Section: Chemical Analysesmentioning
confidence: 99%
“…The finished product is usually of low quality with a high salt content and deteriorates rapidly during retailing and storage (Yankah et al, 1993). There is no report in the literature of microbiological status of momoni.…”
Section: Introductionmentioning
confidence: 98%
“…The pH of the homogenized samples was measured with a pH-meter Model Hm 305 (TOA Electronic, Japan). Salt content was determined according to the method of (Yankah et al, 1993). About 0.5 g of Pelpeledgi was digested in a stomacher with 20 mL of concentrated HNO 3 for 2 h at 100°C on cooling, 100 mL water and 5 mL of ammonium iron sulphate indicator were added and the salt content was determined by titration with a solution of 0, 1 M AgNO 3 which was previously standardized using 0, 1 M standard KCl solution.…”
Section: Surveymentioning
confidence: 99%